Cost Evaluation Of Heart Failure Treatment, Cost-effectiveness Analysis And Budget Impact Of Adding Empagliflozin To Standard Treatment For Heart Failure With Reduced Ejection Fraction - Low, Joo Zheng (2023)
Heart failure (HF) is a clinical condition caused by structural or functional heart abnormalities. The increasing prevalence of HF and frequent hospitalisation due to HF (hHF) significantly impact healthcare expenditure. Moreover, there is limited data on the economic burden of HF across different ejection fractions (EF). Empagliflozin is a novel antidiabetic medication that improves clinical outcomes of HF with reduced ejection fraction (HFrEF) patients. Therefore, this study was designed to determine the cost of HF treatment, cost-effectiveness, and budget impact of adding empagliflozin to the standard of care (SoC) compared to SoC monotherapy from the Ministry of Health Malaysia perspective. A prevalence-based, bottom-up cost analysis study was conducted in three tertiary hospitals in Malaysia to estimate the direct cost and resource utilisation throughout a one-year follow-up. The total costs consisted of outpatient, hospitalisation, medications, laboratory tests, and procedure costs, categorised according to ejection fraction. The cost-effectiveness of empagliflozin was determined using a cohort-based transition states model with health states defined as Kansas City Cardiomyopathy Questionnaire-Clinical Summary Score quartiles and death. The lifetime direct medical costs and quality-adjusted life-years (QALYs) were compared, and the incidence of death and hHF were modelled for each monthly cycle. The clinical inputs and utilities were estimated from the EMPEROR-Reduced trial and supplemented by local costing data.